Polygamy and divorce in Indonesia: the new marriage law - H. Jathar Salij., (Universiti Kebangsaan Malaysia, 1978)
The marriage law which was adopted by the Indonesian Parliament on December 22, 1973 is the product of the Indonesian endeavor to harmonize traditions with modern concepts and of the perseverance of the women who seek equality within the bonds of marriage.